A view of the judgement and interpretation of the international court of justice in the temple of Preah Vihear case - Novaković Marko; Vučić Mihajlo (Međunarodni Problemi, 2014)
On 11th November 2013, the International Court of Justice issued a judgment regarding the request for Interpretation of the Judgment of 15th June 1962 in the case concerning the Temple of Preah Vihear, a border dispute between the Kingdoms of Cambodia and Thailand. In this article, the authors have elaborated both the original judgment and its recent interpretation. They begin by providing the historical context that led to the dispute before the Court. The main part of the article is dedicated to the legal analysis of the judgment and its interpretation. Special attention is given to the Court’s manner of reasoning and the implications which this manner has for the substantial settlement of the dispute and the clarification of several principles of international law that deal with territorial delimitation between states on natural borders, but also to the wider jurisprudence of the Court in similar instances. [Projekat Ministarstva nauke Republike Srbije, br. 179029: Srbija u savremenim međunarodnim odnosima: Strateški pravci razvoja i učvršćivanja položaja Srbije i međunarodnim integrativnim procesima - spoljnopolitički, međunarodni ekonomski, pravni i bezbednosni aspekti]